A modified method for genomic DNA extraction from the fish intestinal microflora - Zhuoran Han; Jingfeng Sun; Aijun Lv; YeongYik Sung; Xueliang Sun; Hongyue Shi; Xiucai Hu; Anli Wang; Kezhi Xing (AMB Express, 2018)
Abstract A modified genomic DNA extraction method named the combination of lysozyme and ultrasonic lysis (CLU) method was used to analyze the fish intestinal microflora. In this method, the physical disruption and chemical lysis steps were combined, and some parameters in the key steps were adjusted. In addition, the results obtained by this method were compared with the results obtained by the Zirmil-beating cell disruption method and the QIAamp Fast DNA Stool Mini Kit. The OD260/OD280 ratio and concentration of the DNA extracted using the CLU method were 2.02 and 282.8 µg/µL, respectively; when the incubation temperatures for lysozyme and RNase were adjusted to 37 °C, those values were 2.08 and 309.8 µg/µL, respectively. On the agarose gel, a major high-intensity, discrete band of more than 10 kb was found for the CLU method. However, the smearing intensity of degraded DNA was lower when the incubation temperatures were 60 °C for lysozyme and 30 °C for RNase than when incubation temperatures of 37 °C for lysozyme and 37 °C for RNase were used. The V3 variable region of the prokaryotic 16S rDNA was amplified, and an approximately 600-bp fragment was observed when the DNA extracted using the CLU method was used as a template. The CLU method is simple and cost effective, and it yields high-quality, unsheared, high-molecular-weight DNA, which is comparable to that obtained with a commercially available kit. The extracted DNA has potential for applications in critical molecular biology techniques.